Microfresamento da liga Ti-6Al-4V com microferramentas com diferentes revestimentos e aplicação de MQL - Ziberov, Maksym (2018)
Titanium alloys have an excellent combination of strength and toughness, low density, high resistance to corrosion and oxidation, besides being non-toxic and biocompatible. These characteristics make them a widely used alternative for the bioengineering field. Ti-6Al-4V titanium alloy is the most used in the market, accounting for about 50% of the total titanium applications. The objective of this work is to study the performance of micro tools 152.4 μm in diameter with different coatings for micromilling of this alloy, as well as the effects of applying minimum quantity of lubrication. Was analyzed the wear, the mechanisms of wear and damage of the micro tool, the formation of burrs, and quantitative and qualitative aspects of the machined surface, such as roughness and scanning electron microscopy, respectively. The results show that the DLC coating has a great effect on the life of the micro tool and the burrs formed. The application of cutting fluid has an effect on the quality of the machined parts, both in terms of qualitative improvement of the surface and in terms of roughness. The dimensions of the burrs formed depend on the cutting conditions, and may have relative dimensions much larger than those of macromilling. Cutting edge rounding, tip wear, and flank wear are the predominant types in microtools. The best performance was that of the DLC coated micro tool under dry conditions, presenting an increase of 640% and 267% when compared to the TiAlN coated microtool and the uncoated microtool, respectively. This is due to the excellent properties of the DLC coating. Dry micromachining showed better results in terms of microtool life and burr height. In dry micromachining with the parameters used in this work, built up edge phenomenon appears for all micro tools, this phenomenon protects wedge against accelerated wear. Due to the low cutting speeds inherent to the process and the small diameter of the micro tool, the built up edge has a great effect on the life of the micromilling.